2007
DOI: 10.1152/ajpendo.00331.2007
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin regulates glucose uptake in BeWo cells

Abstract: Myostatin is a member of the transforming growth factor (TGF)-β superfamily, known for its ability to inhibit muscle growth. It can also regulate metabolism and glucose uptake in a number of tissues. To determine the mechanism of myostatin's effect on glucose uptake, we evaluated its actions using choriocarcinoma cell lines that are widely used as models for placental cells. Protein and mRNA were determined using immunoblotting and RT-PCR/PCR, respectively. Glucose uptake was assessed by uptake of radiolabeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…The effect of myostatin on placental glucose transport is mixed, with decreased glucose transport in a choriocarcinoma cell line (27) and increased transport in human placental explants (28). Myostatin also promotes extravillous trophoblast migration in vitro, which may alter placental development in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of myostatin on placental glucose transport is mixed, with decreased glucose transport in a choriocarcinoma cell line (27) and increased transport in human placental explants (28). Myostatin also promotes extravillous trophoblast migration in vitro, which may alter placental development in vivo (29).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is due solely to increased lean muscle mass or other metabolic effects of reduced circulating myostatin have yet to be determined (33). Recent studies, however, have shown that myostatin inhibits glucose uptake in placental cell lines, suggesting that it may contribute to systemic insulin resistance with obesity (35). Others have implicated myostatin in a network of genes potentially regulated by insulin with extreme obesity (30).…”
Section: Discussionmentioning
confidence: 99%
“…This may contribute to systemic metabolic deterioration of skeletal muscle with the progression of insulin resistance to type 2 diabetes. Diabetes 58: [30][31][32][33][34][35][36][37][38] 2009 O besity and type 2 diabetes are associated with endocrine abnormalities that are either precipitated by or precede the onset of peripheral insulin resistance (1). These include changes in circulating proteins and peptides that produce endothelial dysfunction, low-grade inflammation, and a prothrombotic state, all of which contribute to increased cardiovascular risk (2-4).…”
mentioning
confidence: 99%
“…Mitchell et al (29) have shown that there is a negative correlation in human placenta between myostatin expression and gestational age, with a higher myostatin expression evident in preterm human placental tissues compared with term placental tissues. Additional in vitro studies also found that myostatin regulates glucose uptake in human placenta (3,29).…”
mentioning
confidence: 87%